Research Progress and Clinical Application of TCM Syndrome Differentiation and Treatment of Rheumatoid Arthritis - Yue, Zhao; Wei, Leng (Journal of Contemporary Medical Practice, 2025)
Rheumatoid arthritis (RA) is a chronic, systemic autoimmune disease with a protracted course, high disability, and a significant impact on patients’ quality of life. Traditional Chinese medicine (TCM) offers unique advantages in the treatment of RA, including syndrome differentiation and treatment, holistic regulation, and multi-target intervention, and is widely used in clinical practice. This article systematically reviews the pharmacological research progress of commonly used TCM herbs and representative prescriptions (such as Duhuo Jisheng Decoction and Simiao Yong’an Decoction), covering mechanisms of anti-inflammatory, immunomodulatory, antioxidant, and articular cartilage protection. The safety of drugs such as Tripterygium wilfordii is also discussed. The role of TCM external treatments such as acupuncture, massage, cupping, and fumigation, as well as local interventions such as Chinese herbal plasters and acupoint injections, in RA rehabilitation is further analyzed. The synergistic value of TCM rehabilitation concepts and modern rehabilitation methods is emphasized. Finally, addressing current issues such as inconsistent syndrome differentiation criteria, insufficient research on TCM mechanisms, and the conflict between individualization and standardization, future development directions are proposed, including precise syndrome differentiation, digitally assisted diagnosis, and the development of new TCM dosage forms. This article aims to provide theoretical support and practical references for the comprehensive treatment of RA, promote the integration of traditional Chinese and Western medicine, and enhance overall treatment capabilities.